2013
DOI: 10.1080/00140139.2013.820844
|View full text |Cite
|
Sign up to set email alerts
|

Holding a tablet computer with one hand: effect of tablet design features on biomechanics and subjective usability among users with small hands

Abstract: Different tablet and stylus design features were evaluated for usability and biomechanical properties. On the basis of short-term tasks, emulating functional tablets, usability was improved with the smaller and medium-sized tablets, portrait (vs. landscape) orientation, a back ledge grip and rubberised texture. There were no differences in productivity between design features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Especially, using tablet computers leads to degraded wrist and neck postures, which may increase risk for injury or illness development for these parts of the body. Pereira et al (2013) evaluated the effect of tablet size, orientation, grip shape, texture and stylus shape on productivity, biomechanics, and subjective usability and fatigue associated with holding the tablet with just left hand. This study confined its examinations among users with small hands, because subjects with smaller fingers are likely to be exposed to higher risk of using handheld devices.…”
Section: Physical Impacts Of Laptops and Tablet Pcs On The Msk Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, using tablet computers leads to degraded wrist and neck postures, which may increase risk for injury or illness development for these parts of the body. Pereira et al (2013) evaluated the effect of tablet size, orientation, grip shape, texture and stylus shape on productivity, biomechanics, and subjective usability and fatigue associated with holding the tablet with just left hand. This study confined its examinations among users with small hands, because subjects with smaller fingers are likely to be exposed to higher risk of using handheld devices.…”
Section: Physical Impacts Of Laptops and Tablet Pcs On The Msk Systemmentioning
confidence: 99%
“…Although not directly related with tablet PC use by children, the work of Pereira et al (2013), which considered tablet design features on biomechanics among users with small hands, should also be mentioned here. Because, although the overall hand size of subjects was still bigger than the hand size of children, the study results can give an idea on children's use of same technology.…”
Section: Physical Impacts Of Laptops and Tablet Pcs On The Msk Systemmentioning
confidence: 99%
“…Pereira et al [50] examined various tablet form factors while holding the tablet with the left hand only. When used while standing, for example during walk through inspections of construction sites or entering data into an electronic medical record system in a patient's room, it is expected that the device will be held with the left hand only.…”
Section: Tablet Computers and E-book Readersmentioning
confidence: 99%
“…When used while standing, for example during walk through inspections of construction sites or entering data into an electronic medical record system in a patient's room, it is expected that the device will be held with the left hand only. For this configuration, Pereira et al concluded that smaller to medium size tablets are better in terms of usability, comfort, fatigue, and biomechanics [50].…”
Section: Tablet Computers and E-book Readersmentioning
confidence: 99%
“…Findings of previous works revealed that increasing size of smartphone display make people feel tired because of bad grip comfort (Kietrys et al, 2015;Pereira et al, 2013). Furthermore, usability of smartphone is also deteriorated because of smartphone size (Xiong & Muraki, 2016).…”
Section: Introductionmentioning
confidence: 99%